A shiitake-derived nitrogen/oxygen/phosphorus co-doped carbon framework with hierarchical tri-modal porosity for high-performance electrochemical capacitors. Issue 85 (30th August 2016) - Cao, Hui; Chen, Zhiyi; Chen, Qiuli; Yang, Chao; Hou, Linrui; Rehan, Muhammad; Tong, Liuniu; Yuan, Changzhou
Abstract : A shiitake-derived N/O/P co-doped carbon framework with hierarchical tri-modal porosity was scalably fabricated, and exhibited exceptional supercapacitances, thanks to synergistic contributions from architectural/compositional merits. Abstract : It is greatly significant to develop cost-effective carbons with multi-heteroatom functionalities and hierarchical multi-modal porosity as advanced electrodes for high-performance electrochemical capacitors (ECs). In this contribution, we purposefully proposed a simple yet efficient protocol to scalably fabricate N/O/P co-doped carbon with a hierarchical tri-modal (micro-/meso-/macro-) porosity by utilizing a sustainable natural shiitake as a cheap raw material. Benefiting from intriguing synergistic contributions from the hierarchical porous architecture and compositional merits, the as-fabricated shiitake-derived N/O/P co-doped carbon (SNOPC) exhibited extraordinary electrochemical capacitances with a large specific capacitance (SC) of ∼315 F g −1 at a current rate of 0.5 A g −1 . More strikingly, a gel–electrolyte SNOPC-based symmetric device within a large cell-voltage window of 1.3 V delivered a high energy density of ∼14.4 W h kg −1 at a power density of ∼325 W kg −1, and excellent cycling stability at a large current density. More encouragingly, the elegant design concept, i.e., the smart combination of three-dimensional interconnected hierarchical porosity into the N/O/P co-doped carbon framework, could be easily extended to other low-cost biomass-based carbon materials for next-generation ECs.